The Relationship of Infographic Learning Media and Instagram Media to Students' Digital Literacy Ability in Social Studies Learning at SMP Shidqia Islamic School Bekasi - Fajar Kurniawan; Rudy Gunawan; Lelly Qodariah (Edumaspul: Jurnal Pendidikan, 2022)
This study aims to find a relationship between the use of infographic learning media through Instagram and digital literacy skills in social studies learning for students in class IX SMP Shidqia Islamic School. This quantitative research was conducted at Islamic Middle School Shidqia Bekasi with a total population of 163 students. The data in this study were taken using a questionnaire. The analytical technique used in testing the hypothesis is a correlation test analysis technique. The results showed that: (1) there was a positive and significant relationship between infographic learning media and students' digital literacy skills in social studies learning in Class IX of SMP Islam Shidqia. From the results of the correlation test the results are significant (sig F < 0.05) with a value of R = 0.937 (Very Strong Category). (2) there is a positive and significant relationship between Instagram media and students' digital literacy skills in social studies learning in Class IX of Islamic Middle School Shidqia. From the results of the correlation test the results are significant (sig F < 0.05) with a value of R = 0.952 (Very Strong Category). (3) there is a positive and significant relationship between infographic learning media and Instagram media on students' digital literacy skills in social studies learning in Class IX of SMP Islam Shidqia. From the results of the correlation test the results are significant (sig F < 0.05) with a value of R = 1,000 (Very Strong Category).